(untitled) (Analysis in Theory and Applications, 2017)
In this work, we will prove the existence of bounded solutions in W_0^1,p(Ω) L^∞(Ω) for nonlinear elliptic equations - div(a(x,u, abla u)) + g(x,u, abla u) + H(x, abla u) = f, where a, g and H are Carathéodory functions which satisfy some conditions, and the right hand side f belongs to W^-1,q(Ω).